THE AESTHETIC IMPACT FOR THE TECHNIQUES PRESENTATION - Al -Yousif, Ibrahim jwad; Alkhaiat, Rand Abbas (Iraqi Journal of Architecture and Planning, 2018)
Man searches for a tool to reflect his thoughts and simulate what is around him of features, and through the various and different drawing techniques he can now portray what is around him and demonstrate it with different means as an integral whole. Where using the techniques requires using the experience and skill by drawing and architectural performance. The research problem was determined by the scientific need to know the nature of the aesthetical effect for the presentation techniques in internal architecture, where the research tries to disclose the nature of the aesthetical effect for the presentation techniques through the types of feeling in both the assumptive and realistic spaces, by assuming the effect of the internal architecture by the presentation techniques. And in order to treat the research problem and verify the aims of the research and its hypothesis, an assumptive model was built which represents the items of the presentation techniques, aesthetical effect and internal architecture. The semi-experimental research depended on the phenomenalistic tendency in the remark from designed by the researcher as a means for a test, and a research sample was selected which included four internal spaces within two assumptive spaces and two virtual spaces, and )22 persons as a responding sample, where the sample was divided according to the age category into two parts. Five techniques were applied for each internal space, and the percentage and Excel program for graphs were used in order to reach the best results in harmony with the particularity of the research aims and to verify its adopted assumptions. The results of analyzing the aesthetical effect for the presentation techniques proved many levels, the first level included the relation of the aesthetical effect to the gender where the results showed the strong effectiveness of the water colors techniques + pastel with the males, and the strong effectiveness of the water colors with the females, as for the age category, the results showed the strong effectiveness of the water colors + pastel with the age group (35-50) years and the strong effectiveness of the water colors with the age group (22-35). As for the level of spaces, the results showed the strong effectiveness of the virtual space. The final conclusions showed the strong effectiveness of water colors technique and the weak effectiveness of the ink pen techniques, and the strong effectiveness of the feeling mode effective and the average effectiveness of the mode virtual and weak effectiveness of the mode imaginary, in addition to the strong effectiveness of the virtual space and weak effectiveness of the assumptive space.